Effect of multimode ultrasound assisted extraction on the yield of crude polysaccharides from Lycium Barbarum (Goji) - MUATASIM,Rahma (2018)
Abstract The goals of this exploration were to find out the optimum conditions of ultrasound assisted extraction (UAE) of L. Barbarum crude polysaccharides. Furthermore, to research the impacts of three multi-frequency ultrasound assisted extraction modes on the yield of L. Barbarum crude polysaccharides. The results showed that by applying the traditional single-frequency UAE mode, the optimum extraction time was 30 min, extraction temperature of 60 °C, and solid/liquid ratio of 20 g/600 mL, at a power density of 300 W/L, and ultrasound frequency of 28 kHz. Secondly; a comparison was carried out between three UAE modes using the optimum extraction conditions obtained previously. The energy aggregation counter flow dual-frequency UAE mode gave the highest yield of 38.93% of crude polysaccharides. Followed by the Opposite-sit dual-frequency UAE mode and the energy aggregation counter flow single-frequency UAE mode with yields of 33.60%, and 26.38% of crude polysaccharides, respectively. As a result the ultrasound assisted extraction with dual-frequency mode is more effective for the extraction of L. Barbarum crude polysaccharides. Furthermore, the yield of crude polysaccharides increased by 73.41% using the dual-frequency ultrasound extraction compared to traditional hot water extraction.